Good Government Governance, Pengendalian Intern, Komitmen Organisasi, Gaya Kepemimpinan dan Kinerja Organisasi Perangkat Daerah - Yoga Ananta Pratyaksa, Putu; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi, 2021)
The application of the principles of Good Government Governance, internal control, organizational commitment, and leadership style is very important in organizational management. This study aims to obtain empirical evidence of the effect of Good Government Governance, intellectual control, organizational commitment, and leadership style on the performance of regional apparatus organizations (OPD) in Karangasem Regency. This study uses a quantitative approach using primary data. The sampling method used was saturated sampling technique. The sample used is 3 employees in each regional apparatus organization (OPD) with a total of 32 (OPD). The analysis technique used in this research is multiple linear regression analysis. Based on the results of this study, it shows that the influence of Good Government Governance, internal control, organizational commitment, and leadership style has a positive effect on the organizational performance of OPD Karangasem Regency. Keywords: Good Government Governance; Internal Control; Organizational Commitment; Organizational Performance Leadership Style.